2002
DOI: 10.1159/000048237
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Stimulates Gene Expression of Norepinephrine Biosynthetic Enzymes in Rat Locus coeruleus

Abstract: Gender-specific differences in susceptibility to a number of disorders related to catecholaminergic systems, including depression and hypertension, have been postulated to be mediated, at least in part, by estrogens. In this study, we examined if estrogens may regulate gene expression of norepinephrine biosynthetic enzymes. Administration of five injections of 15 or 40 µg/kg estradiol benzoate to ovariectomized (OVX) female rats elicited a dose-dependent elevation in mRNA levels of tyrosine hydroxylase (TH) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 39 publications
2
84
0
3
Order By: Relevance
“…In a recent study of repeated administration of cocaine, alcohol, or combination, women reported significantly greater ratings for the visual analog "feel good" when cocaine alone was administered, a finding that approached significance for alcohol alone as well (McCanceKatz, Kosten, & Jatlow, 1998b). Moreover, recent evidence suggests that estradiol administration increases DBH in rodents (Serova, Rivkin, Nakashima, & Sabban, 2002). If estrogen stimulates DBH activity in humans, and disulfiram inhibits DBH, the disulfiram effect could possibly be attenuated in women.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of repeated administration of cocaine, alcohol, or combination, women reported significantly greater ratings for the visual analog "feel good" when cocaine alone was administered, a finding that approached significance for alcohol alone as well (McCanceKatz, Kosten, & Jatlow, 1998b). Moreover, recent evidence suggests that estradiol administration increases DBH in rodents (Serova, Rivkin, Nakashima, & Sabban, 2002). If estrogen stimulates DBH activity in humans, and disulfiram inhibits DBH, the disulfiram effect could possibly be attenuated in women.…”
Section: Discussionmentioning
confidence: 99%
“…In LC neurons, estradiol stimulates gene expression of TH and dopamine beta hydroxylase (Serova et al 2002), probably by acting through ER. Besides, it is well established that estradiol induces PRs synthesis in CNS, and that their activation is critical for the LH surge occurrence, since it is blocked by RU-486 administration (Tebar et al 1998).…”
Section: Locus Coeruleusmentioning
confidence: 99%
“…Since LC neurons concentrate estradiol (Heritage et al 1980), express mRNA for ER (Shughrue et al 1997) and PR (Curran-Rauhut & Petersen 2002), and are responsive to estradiol treatment, increasing the expression of noradrenaline synthetic enzymes (Serova et al 2002), it is likely that LC neurons are a target for estradiol action, as described for noradrenergic neurons A1 and A2 (Haywood et al 1999). If so, LC neurons should express ER and, consequently, PR.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in vitro studies have shown that E2, EE2, DES and some catechol-estrogens such as 2-hydroxy-EE2 (2-OH-EE2) and 2-hydroxy-E1 (2-OHE) inhibit NA reuptake sites in synaptosomes from the cerebral cortex and hypothalamus of rats that resulted in increased levels of NA in the synaptic cleft (Ghraf et al, 1983). In line with these findings, acute E2 administration to ovariectomized rats decreased NA reuptake rate in the hypothalamus (Hiemke et al, 1985) and increases mRNA levels of tyrosine hydroxylase in the locus coeruleus (Serova et al, 2002). Finally, it has been reported that estrogens increased NA concentration by inhibiting MAO-A activity (Holschneider et al, 1998).…”
Section: Evidence Of the Interaction Of Estrogens With The Noradrenermentioning
confidence: 68%